2004
DOI: 10.4049/jimmunol.172.4.2296
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Thymocyte Development in Sonic Hedgehog Knockout Embryos

Abstract: The Hedgehog family of secreted intercellular signaling molecules are regulators of patterning and organogenesis during animal development. In this study we provide genetic evidence that Sonic Hedgehog (Shh) has a role in the control of murine T cell development. Analysis of Shh−/− mouse embryos revealed that Shh regulates fetal thymus cellularity and thymocyte differentiation. Shh is necessary for expansion of CD4−CD8− double-negative (DN) thymocytes and for efficient transition from the earliest CD44+CD25− D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
118
4
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(132 citation statements)
references
References 37 publications
8
118
4
2
Order By: Relevance
“…Two of the major cell types that accumulate during cholestatic liver damage, myofibroblastic cells and immature cholangiocytes (ie, bile ductular cells), 1 The possibility that Hh signaling might orchestrate injury responses in adult livers was somewhat unanticipated given present understanding of the Hh pathway. This signaling system is highly conserved across species, and regulates multiple, seemingly disparate, aspects of embryogenesis, including development of the nervous system, 22 heart, 19 thyroid, 20 lung, 16,53 proximal gastrointestinal tract, 17,18,21 and skeleton. 15 Although one study involving embryo explants suggested that Hh activity may also be required for ultimate hepatic specification of primitive cells in the ventral endoderm, 11 the lack of an obvious hepatic phenotype in mice with targeted disruption of various Hh pathway components has cast doubt about the importance of Hh signaling for fetal liver development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the major cell types that accumulate during cholestatic liver damage, myofibroblastic cells and immature cholangiocytes (ie, bile ductular cells), 1 The possibility that Hh signaling might orchestrate injury responses in adult livers was somewhat unanticipated given present understanding of the Hh pathway. This signaling system is highly conserved across species, and regulates multiple, seemingly disparate, aspects of embryogenesis, including development of the nervous system, 22 heart, 19 thyroid, 20 lung, 16,53 proximal gastrointestinal tract, 17,18,21 and skeleton. 15 Although one study involving embryo explants suggested that Hh activity may also be required for ultimate hepatic specification of primitive cells in the ventral endoderm, 11 the lack of an obvious hepatic phenotype in mice with targeted disruption of various Hh pathway components has cast doubt about the importance of Hh signaling for fetal liver development.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody neutralization studies indicated that the myofibroblastic mesenchymal cells produced Hh ligands that enhanced the viability and proliferation of bile ductular epithelial cells, and vice versa (ie, that cholangiocyte-derived Hh ligands promoted growth of the myofibroblastic cells). To our knowledge, this is the first evidence that the Hh pathway, which is well accepted to regulate morphogenesis of various tissues during fetal life, [15][16][17][18][19][20][21][22] plays a role in adult liver repair. This discovery opens a novel area for future research that might help to clarify the pathogenesis of chronic cholangiopathies and lead to novel therapies to improve recovery from bile duct injury.…”
mentioning
confidence: 99%
“…Treatment of mouse fetal thymus organ cultures (FTOCs) with recombinant Shh protein arrested thymocyte development at the DN3 stage after TCR␤ chain rearrangement, whereas neutralization of endogenous Hh signaling by anti-Hh antibody treatment increased DP production. 6,18 In addition, in anti-CD3-treated Rag1 Ϫ/Ϫ FTOCs, differentiation to DP was arrested or enhanced by Shh or anti-Hh treatment, respectively. 6 In contrast to these in vitro experiments, ex vivo analysis of Shh Ϫ/Ϫ fetal thymi on E16.5 suggested that Shh promotes differentiation to the DP stage, 18 as both thymus size and the proportion of DP cells were greatly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,[18][19][20][21][22][23] Analysis of mice mutant for Shh, Gli3, and Smo have shown that Hh signaling is necessary for efficient survival, proliferation, and differentiation of thymocytes at the transition from DN1 to DN2, 18,21,22 but the role of Hh signaling at the transition from DN to DP thymocytes is controversial. Different experimental approaches have produced conflicting results that have led to 3 different interpretations: that Hh is a negative regulator of the pre-TCR signal and differentiation to DP 6,21,24 ; that Shh is a positive regulator of the DN to DP transition 18 ; or that Hh signaling does not influence thymocyte differentiation after the DN2 stage. 22 In vitro studies first demonstrated that Hh signaling influences thymocyte development 6,24 and suggested that Hh signaling was a negative regulator of differentiation to DP cell.…”
Section: Introductionmentioning
confidence: 99%
“…Shh has been shown to regulate the proliferation and differentiation of human hemopoietic precursor cells (23,24). In the thymus, Shh signaling plays an important role regulating thymic cellularity as well as the development of CD4 Ϫ CD8 Ϫ thymocytes (25)(26)(27)(28). In addition, the effector function of peripheral CD4 ϩ T cells is modulated by Shh (29,30).…”
mentioning
confidence: 99%